If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3p + 4)(4p + -5) = 0 Reorder the terms: (4 + 3p)(4p + -5) = 0 Reorder the terms: (4 + 3p)(-5 + 4p) = 0 Multiply (4 + 3p) * (-5 + 4p) (4(-5 + 4p) + 3p * (-5 + 4p)) = 0 ((-5 * 4 + 4p * 4) + 3p * (-5 + 4p)) = 0 ((-20 + 16p) + 3p * (-5 + 4p)) = 0 (-20 + 16p + (-5 * 3p + 4p * 3p)) = 0 (-20 + 16p + (-15p + 12p2)) = 0 Combine like terms: 16p + -15p = 1p (-20 + 1p + 12p2) = 0 Solving -20 + 1p + 12p2 = 0 Solving for variable 'p'. Factor a trinomial. (-4 + -3p)(5 + -4p) = 0Subproblem 1
Set the factor '(-4 + -3p)' equal to zero and attempt to solve: Simplifying -4 + -3p = 0 Solving -4 + -3p = 0 Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3p = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3p = 0 + 4 -3p = 0 + 4 Combine like terms: 0 + 4 = 4 -3p = 4 Divide each side by '-3'. p = -1.333333333 Simplifying p = -1.333333333Subproblem 2
Set the factor '(5 + -4p)' equal to zero and attempt to solve: Simplifying 5 + -4p = 0 Solving 5 + -4p = 0 Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4p = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4p = 0 + -5 -4p = 0 + -5 Combine like terms: 0 + -5 = -5 -4p = -5 Divide each side by '-4'. p = 1.25 Simplifying p = 1.25Solution
p = {-1.333333333, 1.25}
| 5(x-3)=4x+16 | | 30000=30(1+0.06)t | | 6x(12x-3.6)= | | 1/2×=1/4 | | 6(-10-x)-12=10x-104 | | 0=-16t^2+73t+6 | | 4x+4=-4+2x+14 | | -160=t^2+73t+6 | | 234+y=789 | | 3x-18.5=18.5 | | -34=-2/9x | | 6(12x-3.6)= | | -2x+15=10 | | 4y+8=107 | | -4+9x=23 | | 8v+2=10 | | 24x-2=22x | | 30r^2+18ry-5xr-3xy= | | (2x-4)+(2x-4)= | | 14(x)=7(y) | | 2(t+1)+3(4-t)=5 | | x-8=22-4x | | h-5/14=11/14 | | 18x-20y=1800 | | 8x=7-12 | | -7.8b-2.14=-42.7 | | (1+2i)(2+3i)= | | 14d-12d=-84 | | x-8(2x+4)=15x | | 4/5t-8 | | 8ab-9ab= | | 6x-3=2-5x |